A STUDY ON INTRA-RATER RELIABILITY OF STUDENTS’ SELF-ASSESSMENT OF THEIR ENGLISH WRITING - Ida Isnawati (Jurnal Bahasa Lingua Scientia, 2014)
The study is an attempt to estimate the intra-rater reliability of students’ self-assessment of their writing performances and to find out whether rater training improves the reliability. The rater training used is adapted from the model developed by Herman, Aschbacher and Winters(1992). This quantitative study which employed equivalent time-samples design has two variables; they were the reliability coefficient of students’ self-assessment and the rater training. The data were collected by asking 25 students conducting self-assessment on their four writing tasks and analyzed using Spearman coefficient correlation. It was found that the rs were 0.798, 0.772, 0.699 and 0.637; it showed that the consistency within students in assessing their own writing was moderately high. However, the rs of the intra-rater reliability of the self-assessment after the treatments is not higher than that of other experience being available in the absence of the treatment. It is concluded that rater training has not been able to improve the intra-rater reliability.